Febrile Seizures: Clinical Factors Influencing the Length of Hospital Stay - Deniz, Yusuf (The European Research Journal, 2026)
Objectives: This study aimed to identify the clinical factors influencing the length of hospital stay (LOS) in children aged 0–60 months hospitalized with febrile seizures (FS), and to explore potential immunological and psychosocial modulators that may affect hospitalization decisions. Methods: A retrospective observational study was conducted at a tertiary hospital in Karabük, Türkiye, between September 2023 and September 2025. Medical records of patients diagnosed with FS (ICD-10 R56.0) were reviewed using the FONET and e-Nabız systems. Demographic and clinical variables - including age, sex, fever, seizure duration, type (simple/complex), recurrence, infection focus, and presence of seasonal allergic rhinitis (SAR) - were analyzed. Factors associated with LOS were evaluated using multivariable linear regression (P